The Washington decree : a novel - Adler-Olsen, Jussi (Dutton, 2018)
Sixteen years before Democratic Senator Bruce Jansen was elected president of the United States, a PR stunt brought together five very different people: fourteen-year-old Dorothy "Doggie" Rogers, small-town sheriff T. Perkins, single mother Rosalie Lee, well-known journalist John Bugatti, and the teenage son of one of Jansen's employees, Wesley Barefoot. In spite of their differences, the five remain bonded by their shared experience and devotion to their candidate. For Doggie, who worked the campaign trail with Wesley, Jansen's election is a personal victory: a job in the White House, proof to her Republican father that she was right to support Jansen, and the rise of an intelligent, clear-headed leader with her own ideals. But the triumph is short-lived: Jansen's pregnant wife is assassinated on election night.